Analisa Keandalan Sistem Distribusi 20 kV Menggunakan Metode Section Technique dan RIA-Section Technique Pada Sistem Distribusi PT.PLN UP3 Surabaya Utara - Ekamani Putra; Misbahul Munir; Novian Patria Uman Putra; Yulianto Agung Prabowo; Nasyith Hananur Rohiem; Ilmiatul Masfufiah (Institut Teknologi Adhi Tama Surabaya, 2022)
The most basic problem in distributing electrical energy is the quality and availability of electrical energy to consumers. The use of system reliability in a 20 kV distribution network is a very important factor in determining steps that ensure correct handling, as well as the underlying problems in the network, so that these disturbances can be overcome. methods to evaluate a distribution system's reliability index. Its development is very fast. One of them uses the section technique method and the combined RIA-section technique method. The final result of a reliability index is obtained from the sum of each section. But the Section Technique method only uses the failure rate parameter, namely the failure rate with a long enough repair interval (sustained failure rate). The section technique method also has the advantage that it divides the evaluation of the reliability index into small parts, so that ordinary errors can be minimized and also require a short time [1]. The result of the SAIDI Section Technique method is 2.45068492 hours/customer/year. Then, adding the momentary failure rate parameter in the calculation, the SAIDI value is 0.00233399 hours/customer/year. Then in the section technique method, the CAIDI value is 3.150000375 hours/customer/year, but when the momentary failure rate parameter is added, the CAIDI value is 0.00300000 hours/customer/year.